Strategic marketing approaches impact on social enterprises. Issue 7 (2nd August 2021) - Nascimento, Leandro da Silva; Steinbruch, Fernanda Kalil; Oliveira, Daniel Max de Sousa; Costa Júnior, Júlio César da; Luce, Fernando Bins
Abstract : Purpose: Due to social enterprises' (SEs) relevance to social value creation, marketing increases its attention to these hybrid organizations. However, there is no consensus on how strategic marketing can improve SE performance. Thus, this paper aims to discuss how commercial, social and societal strategic marketing approaches relate to compensatory and transformative social entrepreneurship scopes to improve SE performance. Design/methodology/approach: This paper is conceptual. We hold discussions and raise reflections to advance knowledge on both marketing and social entrepreneurship fields, more precisely by intertwining them. Findings: We develop a conceptual model for adapting three strategic marketing approaches to compensatory and transformative SEs. We argue that SEs have three types of performances: commercial, social and societal. Social and commercial strategic marketing are essential for SEs acting in compensating local failures of capitalism. Societal and commercial strategic marketing are essential for SEs focused on transformative actions to changing global system. Such relations can leverage social impact, which we conceptualize as compensatory or transformative. Practical implications: The model contributes to improvements on strategic marketing decisions by marketers and entrepreneurs in social entrepreneurship. Originality/value: We propose a decomposition of strategic marketing into three approaches: commercial, social and societal, which constitutes a novelty to the field. This can facilitate management of SEs with different actions and performances, whether at local or international levels.